2020
DOI: 10.3389/fonc.2020.00705
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Angiogenic and Pro-Inflammatory Regulation by lncRNA MCM3AP-AS1-Mediated Upregulation of DPP4 in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) represents the most common type of renal cell carcinoma (RCC) in adults, in addition to the worst prognosis among the common epithelial kidney tumors. Inflammation and angiogenesis seem to potentiate tumor growth and metastasis of the malignancy. The current study explored the contributions of the lncRNA MCM3AP-AS1 in tumor-associated inflammation and angiogenesis in ccRCC with a specific focus on its transcriptional regulation and its interactions with transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…MCM3AP-AS1 was also found to be upregulated in Burkitt lymphoma, glioblastoma, LC, nasopharyngeal carcinoma, clear cell renal cell carcinoma, pancreatic cancer, and papillary thyroid cancer tissues compared to the corresponding normal tissues (Yang et al, 2017(Yang et al, , 2019Liang et al, 2019;Guo et al, 2020;Li et al, 2020b;Qiu et al, 2020;Sun et al, 2020) In contrast to the above findings, MCM3AP-AS1 expression is markedly downregulated in CSCC tissue samples and predicts a poor outcome. Overexpression of MCM3AP-AS1 reduces CSCC cell proliferation, and MCM3AP-AS1 acts as a tumor suppressor during CSCC development and progression.…”
Section: Other Cancersmentioning
confidence: 70%
See 1 more Smart Citation
“…MCM3AP-AS1 was also found to be upregulated in Burkitt lymphoma, glioblastoma, LC, nasopharyngeal carcinoma, clear cell renal cell carcinoma, pancreatic cancer, and papillary thyroid cancer tissues compared to the corresponding normal tissues (Yang et al, 2017(Yang et al, , 2019Liang et al, 2019;Guo et al, 2020;Li et al, 2020b;Qiu et al, 2020;Sun et al, 2020) In contrast to the above findings, MCM3AP-AS1 expression is markedly downregulated in CSCC tissue samples and predicts a poor outcome. Overexpression of MCM3AP-AS1 reduces CSCC cell proliferation, and MCM3AP-AS1 acts as a tumor suppressor during CSCC development and progression.…”
Section: Other Cancersmentioning
confidence: 70%
“…Qiu et al demonstrated that MCM3AP-AS1 could interact with E2F1 and enhance the enrichment of E2F1 at the DPP4 promoter, increasing the expression of DPP4. As a result, MCM3AP-AS1 promoted angiogenesis and inflammation in clear cell renal cell carcinoma (Qiu et al, 2020). Another study also revealed that MCM3AP-AS1 can recruit DNMT1/DNMT3 (A/B) to induce methylation of NPY1R promoter.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 91%
“…MCM3AP-AS1 was originally reported to be overexpressed in glioblastoma 17 and the up-regulation of MCM3AP-AS1 stimulated cell migration and tube formation of clear cell renal cell carcinoma. 23 MCM3AP-AS1 could also exert a carcinogenic role in hepatocellular carcinoma and papillary thyroid cancer. 20,24 We revealed that MCM3AP-AS1 was aberrantly expressed in CRC tissues and associated with poor prognosis of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that MCM3AP‐AS1 could play a key role in human cancers. MCM3AP‐AS1 was originally reported to be overexpressed in glioblastoma 17 and the up‐regulation of MCM3AP‐AS1 stimulated cell migration and tube formation of clear cell renal cell carcinoma 23 . MCM3AP‐AS1 could also exert a carcinogenic role in hepatocellular carcinoma and papillary thyroid cancer 20,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several angiogenesisregulating lncRNAs such as MANTIS, MEG3, MIAT, MALAT1, and SENCR were shown to have a significant role in angiogenesis and cardiovascular diseases [Yu and Wang, 2018], lncRNA studies conducted in this field are still limited. Significance of several angiogenesis-regulating lncRNAs such as MCM3AP-AS1 [Li et al, 2020;Qiu et al, 2020] have not been uncovered in the development of cardiovascular disease. Accordingly, in this study, we aimed to assess the expression levels of 4 candidate angiogenesis regulating lncRNAs -MEG3, MIAT, MALAT1, and MCM3AP-AS1 -in patients with CAD who underwent coronary angiography and to investigate the diagnostic and therapeutic potentials of these lncRNAs for CAD.…”
Section: Introductionmentioning
confidence: 99%